IoT-Integrated Monitoring System for Environmental Parameters in a Rice Seedling Greenhouse Using ESP32 - Jauharotul Maknunah; Rahajeng Kurnianingtyas (Emitor: Jurnal Teknik Elektro, 2026)
The application of Internet of Things (IoT) technology in modern agriculture has become increasingly important for improving efficiency, productivity, and environmental monitoring. This study presents the design and implementation of an ESP32-based IoT monitoring system for a rice seedling greenhouse. The proposed system was developed to monitor multiple environmental parameters simultaneously, including temperature, soil moisture, pH, and Total Dissolved Solids (TDS) of the nutrient solution. The research employed a Research and Development (R&D) approach involving system requirement analysis, hardware and software design, implementation, IoT integration, and performance evaluation. The hardware architecture consists of an ESP32 microcontroller, DS18B20 temperature sensor, soil moisture sensor, pH sensor, TDS sensor, and an I2C LCD for local data visualization. Sensor data are transmitted via WiFi using the HTTP protocol and displayed in real time through a web-based monitoring platform. Experimental results demonstrated that the developed system successfully acquired, processed, and transmitted environmental data continuously to the monitoring server. Analysis of the collected data showed soil moisture values ranging from 47.8% to 59.1%, temperature values between 28.13°C and 31.69°C, TDS values from 118.22 ppm to 138.02 ppm, and pH values between 3.27 and 13.78. The results also revealed an inverse relationship between temperature and soil moisture, indicating the influence of environmental temperature on water evaporation within the growing medium. Furthermore, the monitoring platform enabled real-time remote supervision and historical data storage, supporting data-driven decision-making for greenhouse management. Overall, the proposed system demonstrates the effectiveness of integrating electronic sensing devices and IoT technology to support smart agriculture applications in rice seedling cultivation.